Travel team : [a novel] - Lupica, Mike. (New York : Puffin, 2006)
After he is cut from his travel basketball team--the very same team that his father once led to national prominence- -twelve-year-old Danny Walker forms his own team of cast- offs that might have a shot at victory.
Subtitle from cover.
979.6
Keywords: Fathers and sons -- Fiction; Schools -- Fiction; Basketball stories; Young adult fiction